PRESERVATION AND REVITALISATION OF THE ENDANGERED GÄ¨KÅ¨YÅ¨ FLUTE - LaRue, Jennifer (International Library of African Music, 2016)
Based on observations, interviews, and recordings collected in Kenya in May-June 2015, this article presents a summary of the search for a nearly "extinct” musical instrument and the need for advocacy research. The måtårårå, originally an oblique bark flute of the Agåkåyå of Kenya, is also made from more durable bamboo and plastic. Initial investigations suggested that the flute was no longer played due to urbanization, modernization of farming techniques, and the loss of certain rituals and dances. Discovery of several elders who still play måtårårå and the process of watching them build and play bark, bamboo, and spider web måtårårås is narrated. The challenges of preserving a tradition when the cultural context for performance no longer exists and potential opportunities for a re-introduction of the måtårårå to contemporary Kenyan culture through intentional curriculum, traditional performances and advocacy in Kenyan cultural centers are discussed.
Keywords: Flute; Musical instruments; Bark Flute (Instrument); Kenya; African Music; Flute (Instrument)